The steel kiss [large type] - Deaver, Jeffery (Deaver, Jeffery. Lincoln Rhyme novel., 2016)
Forced to let a murderer escape so that she can save the life of an accident victim, Amelia Sachs, assisted by forensic detective Lincoln Rhyme, soon discovers that the accident was only the first in a series of deadly attacks.